Osseous Manifestations of Primary Hyperparathyroidism: Imaging Findings - Jackson Bennett; James W. Suliburk; Fanny E. Morón (International Journal of Endocrinology)
Primary hyperparathyroidism is a systemic endocrine disease that has significant effects on bone remodeling through the action of parathyroid hormone on the musculoskeletal system. These findings are important as they can aid in distinguishing primary hyperparathyroidism from other forms of metabolic bone diseases and inform physicians regarding disease severity and complications. This pictorial essay compiles bone-imaging features with the aim of improving the diagnosis of skeletal involvement of primary hyperthyroidism.